Influence of host plant nitrogen fertilization on haemolymph protein profiles of herbivore Spodoptera exigua and development of its endoparasitoid Cotesia marginiventris - Chen, Yigen; Ruberson, John R.; Ni, Xinzhi (My University, 2014)
Nitrogen has complex effects on plant-herbivore-parasitoid tri-trophic interactions. The negative effects of host plant low nitrogen fertilization on insect herbivores in many cases can be amplified to the higher trophic levels. In the present study, we examined the impact of varying nitrogen fertilization (42, 112, 196, and 280 ppm) on cotton plants (Gossypium hirsutum L.) on the interactions between the beet armyworm, Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae), and the hymenopteran endoparasitoid Cotesia marginiventris (Cresson) (Hymenoptera: Braconidae). We predicted that the development and fitness of C. marginiventris would be adversely affected by low host plant nitrogen fertilization through the herbivore S. exigua. The percentage of C. marginiventris offspring developing to emerge and spin a cocoon, and total mortality of parasitized S. exigua larvae were unaffected by nitrogen level. The developmental time of C. marginiventris larvae in S. exigua larvae feeding on low (42 ppm) nitrogen cotton plants was approximately 30% longer than that of those feeding on high (112, 196, and 280 ppm) nitrogen plants. Parasitoid size (length of right metathoracic tibia), a proxy for fitness, of C. marginiventris males was positively affected by nitrogen level. Total amounts of S. exigua haemolymph proteins were not affected by nitrogen level, but were reduced by parasitism by C. marginiventris. Two proteins with molecular weights of ca. 84 and 170 kDa dominated the S. exigua larval haemolymph proteins. Concentrations of the 170 kDa haemolymph protein were unaffected by nitrogen treatment, but parasitism reduced concentrations of the the 170 kDa protein. Concentrations of the 84 kDa protein, on the other hand, were interactively affected by parasitism and nitrogen treatment: higher nitrogen fertilization (112, 196, and 280 ppm) increased protein concentrations relative to the 42 ppm treatment for unparasitized S. exigua larvae, whereas nitrogen treatment had no effects on parasitized larvae. For S. exigua larvae feeding on 42 ppm nitrogen plants, parasitism increased concentration of the 84 kDa protein, while for those feeding on 112, 196, and 280 ppm nitrogen plants, parasitism decreased concentrations of the protein. Possible mechanisms and ecological consequences for the extended development of C. marginiventris on S. exigua hosts grown on low-nitrogen plants are discussed.
Citation: Chen, Y., Ruberson, J. R., & Ni, X. (2014). Influence of host plant nitrogen fertilization on haemolymph protein profiles of herbivore Spodoptera exigua and development of its endoparasitoid Cotesia marginiventris. Retrieved from http://krex.ksu.edu
Keywords: Biological control; Gossypium hirsutum; Tri-trophic interactions